Institutional Review Board Use of Outside Experts: What Do We Know?. Issue 2 (26th February 2022) - Serpico, Kimberley; Rahimzadeh, Vasiliki; Anderson, Emily E.; Gelinas, Luke; Lynch, Holly Fernandez
ABSTRACT: Institutional review boards (IRBs) are permitted by regulation to seek assistance from outside experts when reviewing research applications that are beyond the scope of expertise represented in their membership. There is insufficient understanding, however, of when, why, and how IRBs consult with outside experts, as this practice has not been the primary focus of any published literature or empirical study to date. These issues have important implications for IRB quality. The capacity IRBs have to fulfill their mission of protecting research participants without unduly hindering research is influenced by IRBs' access to and use of the right type of expertise to review challenging research ethics, regulatory, and scientific issues. Through a review of the regulations and standards permitting IRBs to draw on the competencies of outside experts and through examination of the needs, strategies, challenges, and concerns related to doing so, we identify critical gaps in the existing literature and set forth an agenda for future empirical research.